2006
DOI: 10.1253/circj.70.1446
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Procedure for Pulmonary Vascular Obstructive Disease in Down Syndrome With Congenital Heart Disease

Abstract: Background Down syndrome patients are characterized by early progression of pulmonary vascular obstructive disease because of insufficient thickness of the pulmonary arterial media. For those with congenital heart disease (CHD) associated with pulmonary hypertension (PH), a 2-stage procedure of pulmonary artery banding (PAB) and then intracardiac repair (ICR) in early infancy is performed to prevent such pulmonary vascular diseases in early infancy. Methods and ResultsThe subjects were 16 patients with Down sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The incidence and severity of PAH did not significantly differ among patients with Rastelli type C AVSD, as compared with people without DS . A study of lung biopsy results for patients with PAH and pulmonary artery banding reported greater histologic improvement and better prognosis when two‐stage surgical procedures were selected…”
Section: Incidence Of Dsmentioning
confidence: 88%
“…The incidence and severity of PAH did not significantly differ among patients with Rastelli type C AVSD, as compared with people without DS . A study of lung biopsy results for patients with PAH and pulmonary artery banding reported greater histologic improvement and better prognosis when two‐stage surgical procedures were selected…”
Section: Incidence Of Dsmentioning
confidence: 88%
“…A two-stage procedure helped prevent mortality due to obstructive pulmonary vascular lesions, indicating that this procedure was highly recommended [13]. …”
Section: Discussionmentioning
confidence: 99%
“…In the context of cardiac surgery, pulmonary artery banding (PAB) is associated with certain indicators, such as the multiple ventricular septal defects (VSD), 1 VSD with aortic coarctation (COA), 2 univentricular hearts with increased pulmonary blood flow, 3,4 to train the left ventricle before arterial switch operation in certain cases of transposition of the great arteries 5,6 and other rare indicators reported elsewhere. [7][8][9] Historically, PAB had been performed through three surgical approaches; (i) left lateral thoracotomy, (ii) median sternotomy, and (iii) left anterior thoracotomy, 10,11 based on the need for performing additional procedures and the preference of the surgical team.…”
Section: Discussionmentioning
confidence: 99%